2019
DOI: 10.1021/acssuschemeng.9b03781
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Polyphenylene Networks with Tunable Micropores for Hydrogen Storage

Abstract: Micropores, especially ultramicropores with pore size smaller than 1 nm, play a crucial role in hydrogen storage. In this contribution, we report on bulk production of two-dimensional (2D) polyphenylene networks (PPNs) through a solution-based Wurtz reaction. A self-assembled mechanism is proposed for the formation of 2D PPNs based on molecular dynamics simulations. The morphology, structure, surface chemistry, and textural properties of the PPNs are greatly influenced by anneal treatment at 450−550 °C in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…However, it remains challenging to reproduce the excellent transport properties of individual channels at a large scale for practical applications because of the difficulties of perfectly aligning or stacking these materials during the fabrication of membranes 3,24,25 . Two-dimensional (2D) porous carbonaceous materials, such as graphyne-n varieties, 2D polyphenylene networks, and 2D conjugated polymers, have also been explored for separation membranes [26][27][28] because they ideally have channels perpendicular to the molecular plane, and their diameters can be controlled through structural design. For example, theoretical studies predicted that graphdiyne (graphyne-2) could behave as an ideal 2D membrane for chemical and isotopic helium separation 26,29 or water filtration 30 .…”
mentioning
confidence: 99%
“…However, it remains challenging to reproduce the excellent transport properties of individual channels at a large scale for practical applications because of the difficulties of perfectly aligning or stacking these materials during the fabrication of membranes 3,24,25 . Two-dimensional (2D) porous carbonaceous materials, such as graphyne-n varieties, 2D polyphenylene networks, and 2D conjugated polymers, have also been explored for separation membranes [26][27][28] because they ideally have channels perpendicular to the molecular plane, and their diameters can be controlled through structural design. For example, theoretical studies predicted that graphdiyne (graphyne-2) could behave as an ideal 2D membrane for chemical and isotopic helium separation 26,29 or water filtration 30 .…”
mentioning
confidence: 99%
“…The snapshot at the final 200 ps was considered as the final configuration. The total energy of simulation system was computed by using the Ewald method described in detail in reference [41].…”
Section: Methodsmentioning
confidence: 99%
“…[ 102 ] Similarly, 2‐D polyphenylene networks (PPNs) exhibit H 2 uptake (4.28–5.39 mmol g –1 ) at 77 K and 1 bar, owing to the high volume of micropores ≈0.5–0.8 nm. [ 267 ] Gogotsi et al. [ 268 ] reported carbide‐derived carbons with SSA ≈ 3000 m 2 g −1 and gravimetric H 2 storage ≈ 4.7 wt% suggesting that the pores larger than 1.5 nm contribute least.…”
Section: Research Trends and Strategies To Improve Material‐based Hyd...mentioning
confidence: 99%
“…[102] Similarly, 2-D polyphenylene networks (PPNs) exhibit H 2 uptake (4.28-5.39 mmol g -1 ) at 77 K and 1 bar, owing to the high volume of micropores ≈0.5-0.8 nm. [267] Gogotsi et al [268] reported carbide-derived carbons with SSA ≈ 3000 m 2 g −1 and gravimetric H 2 storage ≈ 4.7 wt% suggesting that the pores larger than 1.5 nm contribute least. Linares-Solano et al [269] demonstrated activated carbons and fibers sorbents with 0.6 nm as optimal pore width which can hold two layers of adsorbed H 2 .…”
Section: Optimization Of the Textural Features (Specific Surface Area...mentioning
confidence: 99%